Exosomes derived from pericardial adipose tissues attenuate cardiac remodeling following myocardial infarction by Adipsin-regulated iron homeostasis - Man, Wanrong; Song, Xinglong; Xiong, Zhenyu; Gu, Jing; Lin, Jie; Gu, Xiaoming; Yu, Duan; Li, Congye; Jiang, Mengyuan; Zhang, Xuebin; Yang, Zhi; Cao, Yang; et al. (Frontiers in Cardiovascular Medicine, 2022)
As a vital adipokine, Adipsin is closely associated with cardiovascular risks. Nevertheless, its role in the onset and development of cardiovascular diseases remains elusive. This study was designed to examine the effect of Adipsin on survival, cardiac dysfunction and adverse remodeling in the face of myocardial infarction (MI) injury. In vitro experiments were conducted to evaluate the effects of Adipsin on cardiomyocyte function in the face of hypoxic challenge and the mechanisms involved. Our results showed that Adipsin dramatically altered expression of proteins associated with iron metabolism and ferroptosis. In vivo results demonstrated that Adipsin upregulated levels of Ferritin Heavy Chain (FTH) while downregulating that of Transferrin Receptor (TFRC) in peri-infarct regions 1 month following MI. Adipsin also relieved post-MI-associated lipid oxidative stress as evidenced by decreased expression of COX2 and increased GPX4 level. Co-immunoprecipitation and immunofluorescence imaging prove a direct interaction between Adipsin and IRP2. As expected, cardioprotection provided by Adipsin depends on the key molecule of IRP2. These findings revealed that Adipsin could be efficiently delivered to the heart by exosomes derived from pericardial adipose tissues. In addition, Adipsin interacted with IRP2 to protect cardiomyocytes against ferroptosis and maintain iron homeostasis. Therefore, Adipsin-overexpressed exosomes derived from pericardial adipose tissues may be a promising therapeutic strategy to prevent adverse cardiac remodeling following ischemic heart injury.